STRATEGIES FOR PRESERVING NATIONAL COLOUR IN LITERARY TRANSLATION: A CASE STUDY OF UTKIR HOSHIMOV’S NOVEL “BETWEEN TWO DOORS’’ - Bayjanova Okila Iskandarovna,Inatova Raykhon (International Journal of Literature and Language Studies, 2026)
This article investigates the strategies for preserving national colour in the literary translation of Utkir Hoshimov’s novel “ Between two doors” from Uzbek into English. The study focuses on culture-specific items, kinship terms, forms of address, social realia, idiomatic expressions, proverbs, and ethnographic vocabulary that reflect Uzbek national identity. The research applies descriptive, comparative-linguistic, and linguocultural methods. The analysis shows that the most effective strategies for rendering Uzbek national colour into English are transliteration with explanation, foreignization, descriptive translation, functional equivalence, compensation, and selective footnoting. The article argues that national colour should not be completely domesticated, because excessive adaptation weakens the historical, emotional, and cultural identity of the original text. At the same time, direct transliteration without explanation may reduce readability for English-speaking readers. Therefore, the translator should maintain a balance between cultural authenticity and target-reader comprehension.